2022
DOI: 10.1093/femspd/ftac001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of immunodominant epitopes on nucleocapsid and spike proteins of the SARS-CoV-2 in Iranian COVID-19 patients

Abstract: Given the emergence of SARS-CoV-2 virus as a life-threatening pandemic, identification of immunodominant epitopes of the viral structural proteins, particularly the nucleocapsid (NP) protein and receptor binding domain (RBD) of spike protein, is important to determine targets for immunotherapy and diagnosis. In this study, epitope screening was performed using a panel of overlapping peptides spanning the entire sequences of the RBD and NP proteins of SARS-CoV-2 in the sera from 66 COVID-19 patients and 23 heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
1
12
1
Order By: Relevance
“…Our results showed that the antibody response in BALB/c mice is largely directed against linear epitopes. These findings are different from our previous results obtained from COVID-19 convalescent sera which showed that the antibody response is mainly directed against conformational epitopes of RBD in human ( 42 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Our results showed that the antibody response in BALB/c mice is largely directed against linear epitopes. These findings are different from our previous results obtained from COVID-19 convalescent sera which showed that the antibody response is mainly directed against conformational epitopes of RBD in human ( 42 ).…”
Section: Discussioncontrasting
confidence: 99%
“…It may be due to the higher viral load during early infection in the severe patients that leads to higher antibody levels 116 . In consistence with this finding, we displayed strong reactivity of COVID‐19 patient's sera with a single peptide spanning aa 151–170 located on RNA‐binding terminal domain of N protein, and confirmed this finding by peptide depletion experiments using both ELISA and Western blotting 117 . In contrast, immunisation of Balb/C mice with recombinant N protein showed immunodominance of a peptide spanning aa 391–419 (unpublished data).…”
Section: Epitope Mapping Of B Cell Responses Against N Proteinsupporting
confidence: 75%
“…116 In consistence with this finding, we displayed strong reactivity of COVID-19 patient's sera with a single peptide spanning aa 151-170 located on RNA-binding terminal domain of N protein, and confirmed this finding by peptide depletion experiments using both ELISA and Western blotting. 117 In contrast, immunisation of Balb/C mice with recombinant N protein showed immunodominance of a peptide spanning aa 391-419 (unpublished data). Profiling of another panel of anti-N MAbs (4G3, 5B3, 12B6, 18C7-A2, 21H10-A3, 21H10-E9) by peptide-ELISA and dot-blot assay demonstrated that aa 401-408 constitutes the main linear epitope which is highly conserved among VOIs and VOCs.…”
Section: Epitope Mapping Of B Cell Responses Against N Proteinmentioning
confidence: 98%
“…In a recent study, we performed epitope mapping of RBD in COVID‐19 patients' sera using a panel of linear epitopes spanning RBD. Our results demonstrated involvement of mostly conformational disulfide bond‐dependent epitopes in RBD‐specific IgG antibody 43 . Review of literature for neutralising anti‐SARS‐CoV‐2 MAbs indicates that all reported nAbs recognise epitopes within only the S protein and most of them are directed against the RBD (Figure 3, Table 1).…”
Section: Epitope Mapping Of Neutralising Anti‐sars‐cov‐2 Mabsmentioning
confidence: 57%
“…Identification of the target epitope of an antibody molecule is instrumental in development of effective prophylactic therapeutics and epitope-based vaccines as well as molecular elucidation of MAb neutralising activities. 41,42 In a recent study, we performed epitope mapping of RBD in COVID-19 patients' sera using a panel of linear 43 . Review of literature for neutralising anti-SARS-CoV-2 MAbs indicates that all reported nAbs recognise epitopes within only the S protein and most of them are directed against the RBD (Figure 3, Table 1).…”
Section: Epitope Mapping Of Neutralising Anti-sars-cov-2 Mabsmentioning
confidence: 99%